Prática de ensino em pré-vestibulares populares : um estudo de caso do pré- universitário SEED - Santos, Cátia Matias dos (2011)
This research is about a case study related to the teaching practice in a college preparatory called Pre-Uni supported by Secretaria de Educação de Sergipe (SEED) . It shows the teaching practice in this course through the analysis of organization of teacher‟s work and its methodological specifications. Its main question is: how pedagogic work is organized in the university-daily by SEED? The specifics objectives are analyze the relations among the methodologies of teaching and contents and the fact of being a popular college preparatory course; and identify probable methodological specifications in this practice; to describe and reflect on about the pedagogical purpose of pre-universitario SEED course; to reflect on the access policies of the higher education in Brazil. The theoretical concepts used for affirmative actions; concerning the teaching practices and teachers pedagogic approaches. The subjects of this study were ten teachers who work at Pre-Uni and its pedagogic coordination. In order to guarantee the anonymity of the interviewee, the teachers were identified by letters from A to J and for the pedagogic coordinator, a fake name was used (Aurora). This work has a phenomenological focus and its data were collected through questionnaires, interviews and forms. This dissertation makes up five chapters: the first one is about the spreading of higher education in Brazil; the second one is related to the various ways of entrance exam and the emergence of college preparatory courses; the third one shows educational, teaching and methodological concepts and the fourth one shows the methodological concepts and the characterization of the research object. At last, the final considerations presented focusing on the most relevant aspects for this research. The results show that the teaching practice in a college preparatory course has particular aspects and its organization of contents is influenced by the university where you intend to study at. The strengthening of this teaching practice and its main reasons were observed through the analysis of historian contexts.